Aging alters transcriptional circuitries and SLUG-mediated cellular states of mouse mammary epithelium. - Gross, Kayla. (Tufts University. Tisch Library., 2019)
Age-associated decline in stem cell function predisposes tissues to dysfunction and disease and is driven by disruption of cellular homeostasis. The bulk of age-associated changes to the mammary epithelial epithelium and its stem/progenitor compartments have been studied after the onset of reproductive senescence (menopause) that occurs around midlife, yet nearly half of women in the U.S. are diagnosed with breast cancer before age 62, suggesting that age-associated risk factors for breast cancer development are already present before or after midlife. As such, we sought to investigate the consequences of perimenopausal transition on mammary tissue and stem cell biology. Here we show that middle-aged, perimenopausal mice exhibit facultative stem cell decline, aberrant luminal differentiation in basal cells, and increased genomic and protein stress. Additionally, we demonstrate that young adult mice lacking the transcription factor SLUG/SNAI2 exhibit many of the molecular and cellular features of perimenopause, including facultative stem cell decline, aberrant luminal differentiation in basal cells, and increased DNA damage. Collectively, these results show that the transition to menopause triggers cellular stress that leads to stem cell decline, which is phenocopied by SLUG loss. These findings also link a transcription factor that controls stem cell activity and cell identity to DNA repair and aging.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: Charlotte Kuperwasser.; Committee: Karl Munger, James Schwob, and Lidija Covic.; Keyword: Cellular biology.